Mengelola Bisnis Melalui Pemasaran Holistik dan Syariah pada Masa Pandemi Covid-19 - Lavlimatria Esya; Ganawati Ganawati; Syamsurizal Syamsurizal; Muhammad Faqih; Ayu Trisnawati (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
The Covid-19 pandemic has had a tremendous impact on many sectors of the domestic economy, especially in the micro, small and medium enterprise (MSME) sector. According to the BI report that MSME exporters are the most affected, which is around 95.4% of the total exporters, then the handicraft and tourism supporting sectors are affected by 89.9%. Meanwhile, the smallest sector affected by the Covid-19 pandemic is the agricultural sector, which is 41.5%. From the entrepreneur side, research data from the Ministry of Cooperatives and SMEs reported that MSMEs consisting of wholesalers and retailers experienced the highest impact of the Covid-19 pandemic (40.92%), followed by MSMEs providing accommodation and food and beverages (26.86%) and the smallest sector is the manufacturing sector at 14.25%. Although MSMEs have a lower impact than large entrepreneurs due to Covid-19, MSMEs as business institutions that play a very important role in improving the economy and making a sizeable contribution to the economic development of the people are still affected by Covid-19. On the other hand, MSMEs have many problems, apart from capital, marketing is one of the problems faced by MSMEs during the Covid-19 pandemic. Understanding marketing concepts both holistically and sharia concepts is important for MSMEs to get out of marketing problems during this Covid-19 pandemic. Holistic Marketing is marketing that prioritizes and considers the entire business entity. Where the holistic marketing concept is based on the development, design and implementation of marketing activities, processes and programs that understand the breadth and interrelationships. As for the holistic marketing concept: Relationship, Integrated, Internal, and Performance. Meanwhile, sharia marketing is marketing that is carried out based on sharia principles and contracts. In addition, according to characteristics of Islamic marketing that must be owned by the marketing team are Rabbaniyyah, Akhlaqiyyah, Al-waqiyyah and Insaniyyah.